From Bielefeld to the Unified Patent Court – A Never-Ending Story? - Rudolf Teschemacher; Tilman Müller-Stoy (IIC - International Review of Intellectual Property and Competition Law, 2021)
The authors have known Jochen Pagenberg from different perspectives: Tilman Müller-Stoy for almost 20 years as a partner in the law firm bearing Jochen's name; Rudolf Teschemacher since the start of Jochen's and his own career when both got in touch with IP at the Max Planck Institute in the early 1970s and later on for more than 15 years as a senior consultant at Bardehle Pagenberg. Thus, they paint a colourful picture, in particular throwing a glance at a leitmotiv of his work: European patent litigation.
Keywords: 340; Agreement on a Unified Patent Court; European patent litigation; European Patent Law Agreement; European patent jurisdiction; Rules of procedure; Brexit; Constitutional law issues